2013
DOI: 10.1017/jfm.2012.564
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of edge effects on rotating-disk transition

Abstract: The onset of transition for the rotating-disk flow was identified by Lingwood (J. Fluid. Mech., vol. 299, 1995, pp. 17-33) as being highly reproducible, which motivated her to look for absolute instability of the boundary-layer flow; the flow was found to be locally absolutely unstable above a Reynolds number of 507. Global instability, if associated with laminar-turbulent transition, implies that the onset of transition should be highly repeatable across different experimental facilities. While it has previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 24 publications
5
47
1
Order By: Relevance
“…The theoretical R c found by Lingwood (1995a) for the onset of the absolute instability agrees well with the experimentally observed location for the onset of nonlinearity, R = 502-514 (Lingwood 1996) and R = 510-520 (Imayama, Alfredsson & Lingwood 2013), which indicates that the absolute instability is indeed relevant to the transition process. This is particularly interesting since the rotating-disk flow was the first boundary layer found that exhibited absolutely unstable behaviour, as opposed to, say, flat-plate boundary layers, which are convectively unstable.…”
Section: Figure 1 (Colour Online)supporting
confidence: 80%
“…The theoretical R c found by Lingwood (1995a) for the onset of the absolute instability agrees well with the experimentally observed location for the onset of nonlinearity, R = 502-514 (Lingwood 1996) and R = 510-520 (Imayama, Alfredsson & Lingwood 2013), which indicates that the absolute instability is indeed relevant to the transition process. This is particularly interesting since the rotating-disk flow was the first boundary layer found that exhibited absolutely unstable behaviour, as opposed to, say, flat-plate boundary layers, which are convectively unstable.…”
Section: Figure 1 (Colour Online)supporting
confidence: 80%
“…• , respectively), we employ mathematical approximations, specifically using the assumption of large Reynolds number to expand the scale factors, which eventually lead to the expressions (15) and (16). We also focus on the large spiral wavenumber apparent within the problem, which forms the basis for a small parameter expansion in §asymp.…”
Section: Formulationmentioning
confidence: 99%
“…Although the exact role of local absolute instability in transition over the rotating disk is less clear than originally proposed by Lingwood (1995Lingwood ( ,1996 [see Davies & Carpenter (2003), Pier (2003), Healey (2010), Imayama, Alfredsson & Lingwood (2013)], the theoretical onset of local absolute instability is extremely close to numerous consistent measurements of the onset of turbulence over the rotating disk and this provides a useful of means of comparison. In particular, Garrett & Peake demonstrated that the critical local Reynolds number for local absolute instability is independent of half-angle with R X ≈ 2.5 × 10 5 ; this can be compared to the two sets of experimental results: i) Figure 1 shows the comparison with experimental measurements for the onset of turbulence reported by Kobayashi & Izumi. For cones with ψ ≥ 60…”
Section: Motivation 2 -Experimental Measurements Of the Onset Of Turbmentioning
confidence: 71%